Transverse testicular ectopia found by preoperative ultrasonography. - Nam, Y. S. (Korean Academy of Medical Sciences, 1998)
Transverse testicular ectopia, an extremely rare anomaly, is a deviation of testicular descent resulting in unilateral location of both testes, usually associated with an inguinal hernia, with the spermatic cord of the ectopic testes originating from the appropriate side. In most reported cases, the correct diagnosis was not made preoperatively. But we made a diagnosis of transverse testicular ectopia preoperatively by using the ultrasonography in patient with right-side inguinal hernia and left-side cryptorchism. Left testis was found on the right inguinal area and right testis was found in the right scrotum by ultrasonography, so we could make a diagnosis of transverse testicular ectopia. After right inguinal hemiorraphy, both testes were easily brought down sequentially through the right groin into the scrotum. Left testis was placed in the left hemoscrotum through transceptal incision to the scrotal subdartous pouch.